2011
DOI: 10.3126/ojn.v1i1.9359
|View full text |Cite
|
Sign up to set email alerts
|

Tweed's Diagnostic Facial Triangle for Nepalese Adults

Abstract: A total of 100 lateral cephalograms of the Nepalese adults between the ages of 17 to 30 years were selected from various institutions, communities in Nepal. Cephalograms were traced and measured according to Tweeds descriptions. The results of the study were compared with Caucasians norms established by Tweed. No statistically significant difference between the Nepalese males and females were observed. However, the values were significantly different between Nepalese and Caucasian samples. The mean values for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 17 publications
1
2
0
Order By: Relevance
“…Specific population norms for cephalometric analysis of the Tweed were established too [7]. Similar studies standards cephalometric analysis of Tweed and its components have been carried out for Maratha Ethnic population [14], Nepal [17], Saudi Arabia [21]. Our results, as in presented research results of other authors, point to the need for the creation of Charles H. Tweed International Foundation regulatory framework cephalometric standards based on ethnicity, age and sex.…”
supporting
confidence: 78%
“…Specific population norms for cephalometric analysis of the Tweed were established too [7]. Similar studies standards cephalometric analysis of Tweed and its components have been carried out for Maratha Ethnic population [14], Nepal [17], Saudi Arabia [21]. Our results, as in presented research results of other authors, point to the need for the creation of Charles H. Tweed International Foundation regulatory framework cephalometric standards based on ethnicity, age and sex.…”
supporting
confidence: 78%
“…Among the studies conducted in Nepal, Rajouria EA and colleague reported only 5 (41.6%) patients out of 12 oral LP positive for HCV antibodies but none of their cutaneous form of LP patients showed positive reaction to HCV antibodies whereas Garg VK et al didn't find a correlation between lichen planus and hepatitis c in another study from Nepal. 11,12 In all those studies association of HCV antibody in lichen planus was reported to vary geographically from one to another ranging from 4% to 38%. 13,14 Interestingly no correlation was observed between the viral load and HCV genotypes with the likelihood of developing LP in HCV-infected patients in some of the studies.…”
Section: Discussionmentioning
confidence: 99%
“…Since in different races and ethnicities the characteristics of craniofacial structures vary considerably, this situation is not caused by any curiosity of researchers with regard to the study and creation of a normative basis for teleroentgenographic indices and indices characteristic of a particular ethnic group [3,4,13,17,21]. As these studies indicate significant variations in the various cephalometric indices, the question arises as to the correctness of the application of normative data obtained in the study of another population, for the residents of Ukraine.…”
Section: Introductionmentioning
confidence: 99%